Optimalisasi Literasi Digital sebagai Upaya Menanggulangi Hoax dan Pembangunan Masyarakat Kritis pada Perkumpulan Pemuda Pemudi Kampung Sejahtera - Sukartara, Nirwansyah; Ramadhona, M. Rifqi; Monika, Eka Syafrina; Idaman, Akbar; Gunung, Tar Muhammad Raja (PT Hakhara Akademia Indonesia, 2024)
Kampung Sejahtera is a densely populated area in the river basin of Medan City which often faces challenges in overcoming the spread of false information or hoaxes which can cause confusion and social loss. The lack of digital literacy among their members exacerbates this situation, so efforts are needed to improve their ability to manage digital information effectively. This service aims to optimize digital literacy among Kampung Sejahtera members in order to tackle the spread of hoaxes. Specifically, this service evaluates the current level of digital literacy, identifies types of hoaxes that often circulate, and develops and implements effective digital literacy programs. The effectiveness of the program is evaluated through post-training surveys and observation of member behavior after training. The service shows that members' initial digital literacy level is relatively low, especially in the ability to identify and counter hoaxes. The most frequently spread hoaxes include false information about health, politics and sensational news. After participating in the digital literacy training program, it is hoped that there will be a significant increase in members' ability to recognize and reduce the spread of hoaxes. They become more critical and careful in verifying information before sharing it. Optimizing digital literacy through appropriate training programs has proven effective in tackling hoaxes in Kampung Sejahtera.